2010
DOI: 10.1161/hypertensionaha.108.120295
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Functions of NADPH Oxidases

Abstract: NADPH oxidases belong to a group of enzymes that generate reactive oxygen species (ROS) by electron transfer from NADPH to molecular oxygen. The product of this reaction is the superoxide anion (O 2 Ϫ ), which undergoes secondary reactions. O 2 Ϫ inactivates NO to yield peroxynitrite and spontaneously or under catalysis of superoxide dismutases reacts to hydrogen peroxide. NADPH oxidases, therefore, limit vascular NO availability and facilitate reactions involving ROS. 1 It is now well understood that endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Indeed, the prevention of the production of ROS obviously plays a key role in the appearance of the endothelium-dependent inhibition of the response to phenylephrine in the SHR aorta. This conclusion is based on the observation that the unmasking effect of indomethacin [which limits the production of ROS in this preparation by inhibition of cyclooxygenase (Tang et al, 2007)] is mimicked by apocynin, which acts mainly as a nonselective antioxidant at the concentration used in the present study (Brandes, 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, the prevention of the production of ROS obviously plays a key role in the appearance of the endothelium-dependent inhibition of the response to phenylephrine in the SHR aorta. This conclusion is based on the observation that the unmasking effect of indomethacin [which limits the production of ROS in this preparation by inhibition of cyclooxygenase (Tang et al, 2007)] is mimicked by apocynin, which acts mainly as a nonselective antioxidant at the concentration used in the present study (Brandes, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…However, DPI also can inhibit NADPH oxidases (Griendling et al, 1994), xanthine oxidoreductase (O'Donnell et al, 1993), nitric oxide synthases (Stuehr et al, 1991), and mitochondrial respiration [Complex I (Majander et al, 1994)], all of which could impact on the responses measured in the present study. Different inhibitors of those other enzymes were used to determine whether they would affect the NOS-independent NO release: 1) NADPH oxidase: apocycin, used at a concentration that should inhibit NADPH oxidase besides exerting nonspecific antioxidant properties (Brandes, 2010), decreased rather than increased the contractions evoked by phenylephrine; 2) xanthine oxidoreductase: allopurinol, an inhibitor of xanthine oxidoreductase (Puig et al, 1989) did not reverse the inhibitory effect of the endothelium; 3) nitric oxide synthases: the L-NAME and 1400W experiments already demonstrated that the phenomenon is NOS independent; and 4) mitochondrial respiration (Complex I): Complex III (not Complex I) can transfer nitrite to NO (Kozlov et al, 1999;Nohl et al, 2000), but only in an anoxic environment (Kozlov et al, 1999;Nohl et al, 2000;van Faassen et al, 2009). In the present study, the organ chambers were bubbled with 95% O 2 , which can hardly be considered as an anaerobic condition.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase, which is activated by AT 1 receptor stimulation, is a major source of ROS (11,17,113,135). The specific brain nuclei that regulate SNA, such as the anteroventral third ventricle, paraventricular nucleus of the hypothalamus, NTS, and the RVLM, are rich in AT 1 receptors (2,10,26,28,83).…”
Section: Sympathoinhibitory Effects Of Antihypertensive Drugs and Stamentioning
confidence: 99%
“…Thus, it is possible that AT 1 receptor blockers reduce oxidative stress in the brain, as well as in the peripheral vasculature. It is also possible that AT 1 receptor blockers inhibit ROS production by blocking AT1 receptormediated intracellular signaling (11,48,50) and that this antioxidant action accounts for the absence of reflex-induced sympathoexcitation after treatment with AT 1 receptor blockers. We evaluated the effects of AT 1 receptor blockers, olmesartan and telmisartan, on brain oxidative stress in SHRSP (4,48).…”
Section: Sympathoinhibitory Effects Of Antihypertensive Drugs and Stamentioning
confidence: 99%
“…While low levels of reactive oxygen species (ROS) play a physiological role in cell signalling and vascular function [7], enhanced production or diminished scavenging of these radicals may lead to a reduction in nitric oxide (NO) bioavailability and/or endothelial nitric oxide synthase (eNOS) uncoupling and increased formation of superoxide that are associated with impaired vascular function [8][10]. The protective role of endogenous antioxidant mechanisms in cardiovascular disease and their disturbance in obesity related disorders is less clearly defined [7].…”
Section: Introductionmentioning
confidence: 99%